Warszawskie widowiska aerostatyczne w XVIII i XIX wieku. Wybrane epizody - Kurek, Krzysztof (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
The author presents the history of balloon flights organised in Warsaw in the 18th and 19th centuries. He refers in his reflections to both the history of technology and the history of performance. The aerostat flight spectacles became one of the many elements of metropolitan, democratic and mass-oriented "culture of attrac-tions", co-creating the peculiar panorama of the ludic modernity of nineteenth-century Warsaw. However, the desire for novelty and the intense, never-satisfy-ing-enough experiences associated with it, characteristic of the popular culture of the time, meant that aeronautical displays were enriched with activities that went beyond the "usual" pattern of take-off, flight and landing. The article includes the descriptions and reconstructions of demonstrations by Joseph G. F. Tradini (1850), who used a live animal tied to a balloon with a large number of ropes in-stead of a gondola. Based on press reports, the Warsaw performances of the leg-endary acrobat and gymnast Leona Dare (1887), who performed gymnastic exer-cises on a trapeze while flying at high altitude, arousing the terror and admiration of the observers, have been reconstructed. Autor przedstawia historię lotów balonem organizowanych w Warszawie w XVIII i XIX wieku. Nawiązuje w swoich rozważaniach zarówno do dziejów techniki, jak i historii widowisk. Organizowane pokazy lotów aerostatem stały się bowiem jednym z bardzo wielu elementów wielkomiejskiej, demokratycznej i nastawionej na masowego odbiorcę „kultury atrakcji”, współtworzącej swoistą panoramę ludycznej nowoczesności dziewiętnastowiecznej Warszawy. Jednak charakterystyczne dla kultury popularnej tamtego czasu pragnienie nowości i związanych z nimi intensywnych, nigdy do końca niedających pełnej satysfakcji przeżyć sprawiły, iż pokazy aeronautyczne wzbogacano o działania wykraczające poza „zwyczajny” schemat startu, lotu i lądowania. W artykule znalazły się opisy i rekonstrukcje pokazów Josepha G. F. Tradiniego (1850), który zamiast gondoli wykorzystał żywe zwierzę przywiązane do balonu dużą ilością lin. Na podstawie relacji prasowych zrekonstruowane zostały warszawskie występy legendarnej akrobatki i gimnastyczki Leony Dare (1887), która wykonywała w czasie lotu na dużej wysokości ćwiczenia gimnastyczne na trapezie budząc przerażenie i podziw obserwatorów.
Keywords: historia lotnictwa; historia lotów balonem w XVIII i XIX wieku; widowiska z wykorzystaniem balonów; związki baloniarstwa ze sztuką cyrkową; historia widowisk; history of aviation; history of balloon flights in the 18th and 19th centuries; balloon shows; links between ballooning and circus arts; culture of 19th century attractions; history of shows